Analisis Break Even Point Terhadap Dasar Perencanaan Laba Pada Pt Bumi Sarana Beton Di Makassar - Ahmad Fathur Zaky; Samsinar; Mukhammad Idrus (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2026)
This research was conducted to find out how to do Break Even Point Analysis on the basis of profit planning at PT Bumi Sarana Beton in Makassar in 2021. The variables used in this research consist of two types of variables, namely independent variables and dependent variables. The independent variable in this research is Break even point (X) and the dependent variable in this research is profit planning (Y). The population in this research is the financial report of PT Bumi Sarana Beton. The analysis used to process the results and answer the formulation of this research is descriptive research using the break even point method and profit planning. The research results show that overall in 2021 the sales and production results of PT. Bumi Sarana Beton has passed the break even point both in units and rupiah. The contribution margin achieved by PT Bumi Sarana Beton in Makassar in 2021 is 30%.